COMINGS AND GOINGS: THE MOBILITY OF RURAL POPULATIONS IN PROTECTED AREAS IN THE MIDDLE SOLIMÕES, IN THE BRAZILIAN AMAZON, BETWEEN 2006 AND 2010 - de Oliveira Martins, Maria Isabel Figueiredo Pereira; Nascimento, Ana Claudeise Silva do; Correa, Dávila Suellen Souza; Pereira, Heloisa Correa; Chagas, Hudson Cruz das (Ra’e Ga: o Espaço Geográfico em Análise, 2022)
Population mobility is a subject of investigation that seeks to understand the causes and motives for the occurrence of this process. Understanding population mobility in conservation units of the Brazilian Amazon is important when analyzing the dynamics of individuals and their relation with the occupation of the territory. The purpose of this article was to analyze the origin and destination of population mobility, the motives that prompted the displacements and the demographic profile of the individuals who left and those who arrived to live in the Amanã Sustainable Development Reserve (RDS Amanã), located in the Medium Solimões region in the State of Amazonas. We organized the quantitative information collected in a demographic census conducted in 2011. We verified that 73% of the departures were destined for urban centers, while most of those who arrived to live in the RDS were previously residents of other rural locations. Young people were the principal actors in the departures, mainly in the age group 15 to 20 years old (55%). In terms of arrivals, children and adolescents aged 14 and underrepresented the largest group (38%). Most displacements were for personal reasons and the demand for towns or cities is greater when individuals leave to study, accounting for 95% of departures. Although outgoing migrations were greater than incoming migrations, there was no decrease in the population of the RDS Amanã between 2002 and 2011.